2013
DOI: 10.4081/ni.2013.e17
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β secretion in hippocampal sclerosis patients with mesial temporal lobe epilepsy

Abstract: Mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS) is a common medically intractable epilepsy syndrome. Although pathogenesis of HS still remains highly controversial, genetics may play a role as a predisposing factor. Previous evidence in a Japanese population revealed that the homozygotes for allele T at position -511 of the interleukin (IL)-1β gene promoter region (IL-1β-511 T/T) confers susceptibility to the development of HS. However, whether this polymorphism has an effect on IL-1β levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that GSDMD is activated by the NLRP3 inflammasome, which then cleaves GSDMD to produce GSDMD-N, and GSDMD-N is translocated to the plasma membrane to form a pore; then, the cell membrane swells and ruptures, resulting in the release of cytoplasmic contents and the leakage of mature IL-1β and IL-18 (Ding et al, 2016). Studies have shown that the levels of IL-1β are elevated in dogs with epilepsy (Kostic et al, 2019) and in hippocampal sclerosis patients with mesial temporal lobe epilepsy (Dundar et al, 2013). We found that agmatine could reduce the expression of NLRP3, ASC, caspase-1 and IL-1β at the protein and mRNA levels, and inhibit the release of IL-1β in serum and supernatant, thus inhibiting neuroinflammation, GSDMD activation, and pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that GSDMD is activated by the NLRP3 inflammasome, which then cleaves GSDMD to produce GSDMD-N, and GSDMD-N is translocated to the plasma membrane to form a pore; then, the cell membrane swells and ruptures, resulting in the release of cytoplasmic contents and the leakage of mature IL-1β and IL-18 (Ding et al, 2016). Studies have shown that the levels of IL-1β are elevated in dogs with epilepsy (Kostic et al, 2019) and in hippocampal sclerosis patients with mesial temporal lobe epilepsy (Dundar et al, 2013). We found that agmatine could reduce the expression of NLRP3, ASC, caspase-1 and IL-1β at the protein and mRNA levels, and inhibit the release of IL-1β in serum and supernatant, thus inhibiting neuroinflammation, GSDMD activation, and pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The role of inflammation and oxidative stress in the pathogenesis and exacerbation of disease should not be overlooked. IL-1B is known to be an important inflammatory marker and is found to induce epilepsy by inducing inflammation in the brain ( Olgac Dundar et al, 2013 ). The increased levels of IL-1B could also flare an aggravated inflammatory response including TNF-α release, which itself is able to regulate the synaptic transmission, thus affecting the neural system excitability ( Kumar et al, 2007 ; Tiwari et al, 2012 ).…”
Section: Black Pepper ( Piper Nigrum (L) [Piperace...mentioning
confidence: 99%
“…The IL-1 gene cluster on chromosome 2q12-13 contains three related genes, IL-1alpha , IL-1beta , and IL-1RN . A common C/T SNP of the IL-1beta promoter at position −511 has been found to correspond with altered IL-1beta protein expression both in vitro and in vivo [ 13 ].…”
Section: Introductionmentioning
confidence: 99%